Extension to Alpha Algorithm for Process Mining (International Journal of Engineering and Computer Science, 2015)
Different Enterprise Information Systems store relevant information about the events occurring in the enterprise. The information stored may be of data, process, etc. and is well structured.  The stored information paves the path for Process Mining. Many approaches are suggested for Process Mining, out of which the core approach is algorithmic approach. In Process Mining, Alpha Algorithm assumes importance as it aims at reconstructing causality, from a set of sequences of events that take place in an organization. The paper focuses on identifying limitations of Alpha Algorithm and giving an extension to increase its functionality.